Effect of oil price on economic growth and exchange rate in Malaysia - Karunanithi, Kriskkumar (2019)
This study investigates the effect of oil price on the economic growth and exchange rate for the case of Malaysia. The recent innovative cointegrating nonlinear autoregressive distributed lag (NARDL) model of Shin et al. (2014), which is the extended version of the autoregressive distributed lag (ARDL) model of Pesaran et al. (2001), is used to analyse the relationships. This technique allows short-run and long-run nonlinearities through the decomposition of the oil price into partial sums of positive and negative changes while maintaining the advantages of a typical ARDL. For the oil price-growth nexus, annual data that covers from 1981 to 2014 is employed. Results show that the effect of oil price on growth is insignificant in a linear model. However, when a nonlinear model is estimated, the results revealed that the asymmetric effect does indeed exist. A decrease in oil price does contribute to economic growth, while an increase in oil price does not. The findings would suggest that Malaysia is not able to reap the benefit from an increase in oil price and at the same time, a decrease in oil price reduces the cost of production, thus spurring the economic activities. As such, policymakers should ensure that proper measures are in place to ensure that oil revenues are channelled to productive purposes while also ensuring that Malaysian will continue to benefit from the decrease in oil price. In addition, for the oil price-exchange rate nexus, the ARDL and NARDL approach is employed as well. Using data from 1982: Q1 to 2016: Q4, results show that the asymmetric effect is not present in this case. However, for a linear model, the effect of oil price on the real effective exchange rate is positively significant, indicating that an increase in oil price leads to an appreciation of the Malaysian currency relative to other countries. This suggests that the oil markets play a vital role in influencing the movement of the exchange rate, particularly the Malaysian ringgit. As such, monetary policies should still take oil price into consideration to avoid extreme fluctuations in a case of large oil price shocks despite the non-existent of asymmetry. Overall, as an oil-exporting country, Malaysia is still reliant on crude oil and policymakers should account for the crude oil price in the formulation of policies given the significance of crude oil as a determinant of economic growth and the exchange rate.